327 ROPPORIN IS A NOVEL CANCER TESTIS ANTIGEN FOR MULTIPLE MYELOMA. Issue 1 (1st January 2007) - Chiriva-Internati, M.; Ferrari, R.; Kelly, A.; Yuefei, Y.; Cobos, E.
Abstract : Purpose: Multiple myeloma (MM) is a hematologic disease characterized by plasma B-cell high proliferation in the bone marrow environment, osteolysis, local angiogenesis, and distant metastasis. MM remains a fatal malignancy mainly due to the development of intrinsic and acquired drug resistance. To develop an alternative cure based on immunotherapy, the discovery of new possible targets is needed. A potential immunotherapeutic marker displays low and/or restricted expression in normal tissues and high levels of expression in malignant tissues. Ropporin is exclusively expressed in testis and induced at the late stage of spermatogenesis. Immunocytochemistry, using anti-ropporin antibody, showed that ropporin is localized in the principal piece and the end piece of sperm flagella. Electron-microscopy revealed that ropporin is mostly localized in the inner surface of the fibrous sheath. Our aim was to investigate the presence of ropporin as a novel cancer testis antigen target in MM patients. Methods: We evaluated ropporin expression in a normal panel of tissues and in 15 MM patients both at the transcriptional and at the protein level by PCR and by immunohisto-/cytochemistry. The normal investigated tissues were kidney, ovary, skeletal muscle, mammary, brain, heart, colon, stomach, liver, lung, pancreas, spleen, trachea, and bone marrow. Summary: The analysis of ropporin mRNA expression did not show bands in the panel of normal tissues, whereas positive band signals were detectable in 5 of the 15 investigated patients (33.3%). The normal panel, investigated by immunohistochemistry, showed no staining for any of the organs evaluated expect the positive control (testis), whereas 6 of the 15 MM patients (40%) showed a positive reaction after immunocytochemical treatment. Conclusion: We established for the first time that ropporin is expressed at the transcriptional level in MM, with a rate of 33.3%, and at the protein level, in the 40% of the examinated cases, whereas it was not shown in normal tissues, neither at the transcriptional nor at the protein level. Interestingly, the PCR data were confirmed and reinforced by immunocytochemistry. Since ropporin has been shown to be exclusively expressed in the testis and in no other normal tissue, our data strongly suggest that ropporin could be a novel cancer testis antigen and possibly a suitable immunologic target for MM.